The Human Suffering caused by bomb containing White Phosphorus: Health Effects - Rukhshan Khurshid, Haleema Sajid, Huma Ashraf, Sadia Majeed, Farah Hanif, Shazia Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: White phosphorus cause injuries and bereavement by burning human body, by being inhaled the smoke or body exposed to burning material. Aim: To find out the Human Suffering caused by bomb containing White Phosphorus: Health effects Methodology: An Exploratory Surveys (case control study) was carried out on people who exposed to bomb blasts (white phosphorous) and shooting happened in a market of Lahore. Data was collected from 100 consented victims residing in the terrorism-affected area. The detail of personal data and health effects was recorded in a Proforma. A chi-squared test showed the differences in complains of victims on exposure. Results: Of the one hundred patients majority was male with age < 30 years and were exposed to explosion in open air space.The highest odds of feeling generalized weakness, susceptibility to fatigue was observed followed by psychological trauma, Insomnia in initial days, scared to dark and scared to close door was noted. Other complains of victims wereear drum rupture, with highest odds and it was followed by head injuries, brain injuries, head injuries causes blindness and hair loss due to shelling. Conclusion: In populated placed heavy explosive weaponries increase the risk of personal and emotional harm to general people.